Probing Hydrodynamics in PbPb Collisions at 5.02 TeV with Higher-order Cumulants - Dattamunsi Aryaa (EPJ Web of Conferences, 2025)
The elliptic flow of charged hadrons is studied through multiparticle correlations in PbPb collisions at √sNN = 5.02 TeV, corresponding to an integrated luminosity of 0.607 nb−1. v2 {2k} are measured up to the tenth order (k = 5) as functions of the collision centrality. They are shown to follow the ordering : v2{2} > v2{4} ≳ v2{6} ≳ v2{8} ≳ v2{10}. The centrality-dependent moments - skewness, kurtosis and, for the first time, superskewness, are measured for the fluctuation-driven event-by-event v2 distribution. These moments can be good probes of the initial-state geometry in high-energy nucleus-nucleus collisions, assuming a hydrodynamic expansion.